2011
DOI: 10.3324/haematol.2011.050096
|View full text |Cite
|
Sign up to set email alerts
|

Long-term follow up after allogeneic stem cell transplantation in patients with severe aplastic anemia after cyclophosphamide plus antithymocyte globulin conditioning

Abstract: The online version of this article has a Supplementary Appendix. BackgroundDue to increased rates of secondary solid organ cancer in patients with severe aplastic anemia who received an irradiation-based conditioning regimen, we decided some years ago to use the combination of cyclophosphamide and antithymocyte globulin. We report the long-term follow up of patients who underwent hematopoietic stem cell transplantation from an HLAmatched sibling donor after this conditioning regimen. Design and MethodsWe analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 45 publications
2
38
2
Order By: Relevance
“…30 Moreover, the low occurrence of tumors after MFD transplant is in keeping with that seen in recent studies with a longer follow up. 31 However, given the young age of our patients, tumor occurrence needs to be carefully monitored during long-term follow up. Reports in literature indicate that a second course of IST after previous failure provides an overall success rate of 30-70% 3,32-34 but a far weaker hematopoietic reconstitution than after HSCT.…”
Section: Discussionmentioning
confidence: 99%
“…30 Moreover, the low occurrence of tumors after MFD transplant is in keeping with that seen in recent studies with a longer follow up. 31 However, given the young age of our patients, tumor occurrence needs to be carefully monitored during long-term follow up. Reports in literature indicate that a second course of IST after previous failure provides an overall success rate of 30-70% 3,32-34 but a far weaker hematopoietic reconstitution than after HSCT.…”
Section: Discussionmentioning
confidence: 99%
“…10 Chronic GVHD (cGVHD) remains a problem for 30-50% of patients, and this impacts not only on survival but also on quality of life after HSCT. 8,18 Risk factors for cGVHD include older age, previous acute GVHD (aGVHD) and PBSC source. 19,20 Alemtuzumab, a CD52 MoAb, has been evaluated in a multicenter retrospective study in 50 patients receiving a MSD or MUD transplant for SAA.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to HSCT for haematological malignancy, graft failure remains a significant problem in SAA, especially in patients, who have been heavily transfused and are alloimmunized to major and minor HLA antigens. Graft failure occurs in up to 10 % of MSD and 15 % of MUD HSCT patients [3,6,8,10].…”
Section: Alemtuzumab: the Humanized Form Of Campath-1 Antibodiesmentioning
confidence: 99%
“…A recent retrospective EBMT study of 1,886 patients showed that the addition of ATG improved OS after MSD HSCT [6]; a previous prospective randomized study from the CIBMTR showed no significant difference in OS when ATG was added to CY 200 mg/kg, but that study was underpowered due to relatively low number of patients enrolled [4]. However, ATGbased conditioning is associated with up to 30 % incidence of chronic GVHD [3][4][5][6], and severe chronic GVHD impacts quality of life as well as OS (Table 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation